“Oh, Deep in My Heart, I Do Believe …” Elements of a Missionary Spirituality for Redressing Racism - Guider, Margaret Eletta (Missiology, 2004)
This theological reflection draws together insights shared during the 2003 Annual Meeting of the American Society of Missiology. Guider argues that every missionary effort to redress racism and racial privilege is an evangelical endeavor of the will, anchored in hope and predicated on the love of goodness. The reflection explores the correlation between three biblical points of reference and challenges faced by missionaries individually and collectively. It articulates a synthetic statement of faith for missionaries committed to racial harmony and justice, using insights from John Duns Scotus as well as a critical reappropriation of the doctrine of imago dei. The reflection concludes by responding to the question, “What does it mean for missionaries to be found worthy of trust in a racist world?”